An Improved Land Biosphere Module for Use in the Dcess Earth System Model (Version 1.1) with Application to the Last Glacial Termination - (:unkn) unknown (COPERNICUS GESELLSCHAFT MBH, 2017)
Interactions between the land biosphere and the atmosphere play an important role for the Earth s carbon cycle and thus should be considered in studies of global carbon cycling and climate. Simple approaches are a useful first step in this direction but may not be applicable for certain climatic conditions. To improve the ability of the reduced-complexity Danish Center for Earth System Science (DCESS) Earth system model DCESS to address cold climate conditions, we reformulated the model s land biosphere module by extending it to include three dynamically varying vegetation zones as well as a permafrost component. The vegetation zones are formulated by emulating the behaviour of a complex land biosphere model. We show that with the new module, the size and timing of carbon exchanges between atmosphere and land are represented more realistically in cooling and warming experiments. In particular, we use the new module to address carbon cycling and climate change across the last glacial transition. Within the constraints provided by various proxy data records, we tune the DCESS model to a Last Glacial Maximum state and then conduct transient sensitivity experiments across the transition under the application of explicit transition functions for high-latitude ocean exchange, atmospheric dust, and the land ice sheet extent. We compare simulated time evolutions of global mean temperature, pCO(2), atmospheric and oceanic carbon isotopes as well as ocean dissolved oxygen concentrations with proxy data records. In this way we estimate the importance of different processes across the transition with emphasis on the role of land biosphere variations and show that carbon outgassing from permafrost and uptake of carbon by the land biosphere broadly compensate for each other during the temperature rise of the early last deglaciation.